2021
DOI: 10.3390/ijerph18095037
|View full text |Cite
|
Sign up to set email alerts
|

Different Time Scale Distribution of Negative Air Ions Concentrations in Mount Wuyi National Park

Abstract: The concentration of negative air ions (NAIs) is an important indicator of air quality. Here, we analyzed the distribution patterns of negative air ion (NAI) concentrations at different time scales using statistical methods; then described the contribution of meteorological factors of the different season to the concentration of NAIs using correlation analysis and regression analysis; and finally made the outlook for the trends of NAI concentrations in the prospective using the auto regressive integrated movin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…NAIs concentration and Ta showed marked piecewise characteristics, with NAIs increasing linearly with rising Ta only if the Ta was separated into three ranges of − 5 to 10 °C, 10 – 30 °C, and 30–40 °C. NAIs concentration was correlated with RH spanning all seasons, and water was an important factor affecting the distribution of NAIs concentration in different time series, as Li C et al reported (Li C et al 2021 ). Additionally, Peng LY et al found that the NAIs concentration in different garden types has a differing correlation with Ta, RH, and precipitation, but that both are positively correlated with rainfall.…”
Section: Overview Of Naismentioning
confidence: 68%
“…NAIs concentration and Ta showed marked piecewise characteristics, with NAIs increasing linearly with rising Ta only if the Ta was separated into three ranges of − 5 to 10 °C, 10 – 30 °C, and 30–40 °C. NAIs concentration was correlated with RH spanning all seasons, and water was an important factor affecting the distribution of NAIs concentration in different time series, as Li C et al reported (Li C et al 2021 ). Additionally, Peng LY et al found that the NAIs concentration in different garden types has a differing correlation with Ta, RH, and precipitation, but that both are positively correlated with rainfall.…”
Section: Overview Of Naismentioning
confidence: 68%
“…Forests can ionize the surrounding air and release free electrons, which combine with oxygen molecules to form negative air ions. Negative oxygen ions (NAIs) are individual molecules or light ion clusters that carry a negative charge in the atmosphere [1]. They are specifically called negative oxygen ions due to oxygen's exceptional ability to capture free electrons and its inherent inclination to acquire them [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of investigation on urban forest healthcare benefits has focused on the evaluation and analysis of individual healthcare factors such as negative air ions (Li et al, 2021;Shi et al, 2021), phytoncide (Antonelli et al, 2020;Woo and Lee, 2020), human comfort (Jeong et al, 2016;Rahman et al, 2020) and so on. Only a few scholars, such as Han et al (2012), Zhao et al (2019), Wen (2020), Yang et al (2022), and the team of Cheng Wang (Gu, 2013;Wang et al, 2018), have comprehensively considered the forest healthcare benefits of several indicators such as negative air ion concentration, air oxygen content, human comfort index, airborne particulate matter concentration, airborne bacteria content, noise level, and phytoncide relative content, providing a vital theoretical basis for the study of comprehensive healthcare benefits of forest communities.…”
Section: Introductionmentioning
confidence: 99%